Ranking of Closeness Centrality for Large-scale Social Networks - Okamoto, Kazuya; Chen, Wei; Li, Xiang-Yang (Proceedings of the 2nd International Frontiers of Algorithmics Workshop (FAW'2008), Changsha, China, June 2008., 2008)
Closeness centrality is an important concept in social network analysis. In a graph representing a social network, closeness centrality measures how close a vertex is to all other vertices in the graph. In this paper, we combine existing methods on calculating exact values and approximate values of closeness centrality and present new algorithms to rank the top-k vertices with the highest closeness centrality. We show that under certain conditions, our algorithm is more eﬃcient than the algorithm that calculates the closeness-centralities of all vertices.